Evaluation of effectiveness of atorvastatin in treating chronic subdural hematoma not requiring surgery: A meta-analysis of randomized controlled trials - Bo Wang; Kangqi Li; Chenyu Guo; Zhe Wang; Weiwei Zhu; Congxiao Lu (Annals of Indian Academy of Neurology, 2024)
Chronic subdural hematoma (CSDH) is a chronic space-occupying lesion formed by blood accumulation between the arachnoid membrane and the dura mater. Atorvastatin is of increasing clinical interest for CSDH. We performed a meta-analysis of published randomized controlled trials (RCTs) and used objective data as the primary outcomes to provide an evidence-based analysis of the efficacy of atorvastatin for CSDH treatment. Databases of MEDLINE (via PubMed), EMBASE, the Cochrane Library, Scopus, Web of Science, ScienceDirect, Chinese National Knowledge Infrastructure (CNKI), Cqvip database (CQVIP), and Wanfang database were systematically searched for RCTs reporting the use of atorvastatin for CSDH treatment. Odds ratio (OR), standard mean difference (SMD), and 95% confidence intervals (CIs) were used as summary statistics. I-square (I2) test was performed to assess the impact of study heterogeneity on the results of the meta-analysis. Nine relevant RCTs with 611 patients were identified for inclusion in this meta-analysis. Compared to controls, atorvastatin treatment had a significantly higher effectiveness (OR: 7.41, 95% CI: 3.32-16.52, P < 0.00001, I2 = 0%), lower hematoma volume (SMD: −0.46. 95% CI: −0.71 to −0.20, P = 0.0005, I2 = 0%), higher activities of daily living-Barthel Index (ADL-BI) (SMD: 2.07, 95% CI: 1.06-3.09, P < 0.0001, I2 = 92%), and smaller Chinese stroke scale (CSS) (SMD: -1.10, 95% CI: −1.72 to −0.48, P = 0.0005, I2 = 57%). In view of these findings, we conclude that the outcomes of experimental group are superior to the control group with respect to effectiveness, hematoma volume, ADL-BI, and CSS based on nine RCTs with 611 patients. Atorvastatin is beneficial to CSDH patients without surgery.